2020
DOI: 10.1186/s12873-020-00310-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum Copeptin levels in the emergency department predict major clinical outcomes in adult trauma patients

Abstract: Background: Early prognostication in trauma patients is challenging, but particularly important. We wanted to explore the ability of copeptin, the C-terminal fragment of arginine vasopressin, to identify major trauma, defined as Injury Severity Score (ISS) > 15, in a heterogeneous cohort of trauma patients and to compare its performances with lactate. We also evaluated copeptin performance in predicting other clinical outcomes: mortality, hospital admission, blood transfusion, emergency surgery, and Intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(58 reference statements)
3
2
0
Order By: Relevance
“…Another study reported that in patients with multiple traumas requiring ICU admission, both copeptin and AVP exhibited peak levels on ED admission followed by a significant decrease within 24 hours but remained above the detection limit 15 . An elevated copeptin level also indicated the need for transfusion in trauma patients 14,16 . These findings were reproduced in our study, where copeptin performed better than scoring models in predicting severity and mortality.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Another study reported that in patients with multiple traumas requiring ICU admission, both copeptin and AVP exhibited peak levels on ED admission followed by a significant decrease within 24 hours but remained above the detection limit 15 . An elevated copeptin level also indicated the need for transfusion in trauma patients 14,16 . These findings were reproduced in our study, where copeptin performed better than scoring models in predicting severity and mortality.…”
Section: Discussionsupporting
confidence: 82%
“…15 An elevated copeptin level also indicated the need for transfusion in trauma patients. 14,16 These findings were reproduced in our study, where copeptin performed better than scoring models in predicting severity and mortality.…”
Section: Discussionsupporting
confidence: 77%
“…[39,118]. A meta-analysis including 2654 patients from 17 studies has recently confirmed previous findings, demonstrating not only a significant association between increased plasma copeptin levels and TBI, but also copeptin is of prognostic value in predicting brain concussion, progressive hemorrhagic injury, acute traumatic coagulopathy, mortality and poor functional outcomes in patients with TBI (AUC 0.83-0.90) [119].…”
Section: Neurological Illnessessupporting
confidence: 62%
“…Although the serum copeptin and prolactin concentrations were increased in both febrile seizures and epileptic seizures in contrast with serum neuro-filament light chain, the authors could not confirm them as prognostic biomarkers as neither of them was correlated with recurrent seizures [59]. In a group of 125 mixed trauma patients, copeptin was found as a precise prognostic and diagnostic biomarker over lactate, where it showed more accuracy in hospital admission prediction, blood transfusion, and identification of patients with injury severity score (ISS) > 15 than lactate [60]. More recently, in a meta-analysis including 17 studies and 2654 participants with Traumatic brain injury, the authors suggested that copeptin could be a useful prognostic and diagnostic biomarker for Traumatic brain injury [61].…”
Section: Evidence Of Copeptin In Modulating the Risk Of Neurological ...mentioning
confidence: 95%